2012
DOI: 10.4103/2278-960x.104298
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche and menstrual problems among school-going adolescent girls of a North Indian district

Abstract: Background: Menstruation and related problems are difficult issues for adolescent girls and are a common reason for consulting healthcare providers. Objectives: To study age at menarche and menstrual problems among school girls in Lucknow district of north India. Materials and Methods: A cross-sectional study was carried out in urban as well as rural schools of Lucknow district from October 2008 to September 2009. Multistage random sampling was used to select the requisite number of girls. A total of 847 schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
5
19
0
Order By: Relevance
“…This is similar to observation by Sachan et al 5 were dysmenorrhoea was seen in 73.7% of girls. Almost similar finding was reported by Agarwal et al 11 in adolescent girls (79.6%).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This is similar to observation by Sachan et al 5 were dysmenorrhoea was seen in 73.7% of girls. Almost similar finding was reported by Agarwal et al 11 in adolescent girls (79.6%).…”
Section: Resultssupporting
confidence: 81%
“…As the girls of urban schools in my study area were more oriented in academic activities than the girls of rural schools leading to stress. Similar finding was observed by Sachan et al, 5 where menstrual cycle irregularity was 24.7% in urban school girls and 18.1%. in rural school girls.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This result comes in accordance to the results from other studies conducted in North Indian District, which illustrated that the menarche mean age was 12.84 ± 1.4 years [13]. Another study done at El-Mansoura city [12,14], Egypt, the mean age of menarche was 12.9 years.…”
Section: Discussionsupporting
confidence: 82%
“…27 In our study we found that the majority of girls of government school were using clothes (36.8%) or both clothes and sanitary pads (35.6%) as an absorbent material during their menstrual cycle. This situation was a little better in the non-government school girls where the percentage of girls using sanitary pads alone was 65.2%; though 25.2% girls were still making use of both clothes and sanitary pads.…”
mentioning
confidence: 78%